Two new species in the Drosophila flavopilosa and Drosophila morelia species groups (Diptera: Drosophilidae) in the eastern Andes of Ecuador - Ramos Guillín, Emily (2018)
One species in the Drosophila flavopilosa species group and another in the Drosophila morelia species group (Diptera: Drosophilidae) are described and illustrated. The larvae of the flies in these groups develop exclusively in flowers and, usually, are rarely collected from rotten plant parts. However, in this case, these new species were not collected from flowers but were captured with fermented banana and yeast. It indicates that this species may be attracted to the odors of yeast fermentation and not only solanaceous flowers. The specimens were collected at 3362 m above sea level. There are four species of the Drosophila flavopilosa species group and one species of the Drosophila morelia species group previously described from Ecuador. The new species are: Drosophila pseudokorefae sp. nov. in the Drosophila flavopilosa species group and Drosophila pseudomorelia sp. nov. in the Drosophila morelia species group.